NILAI ETIKA DALAM BUKU KUMPULAN CERITA RAKYAT DARI JAMBI 2 KARYA KASLANI - Nurul Hikmah; Erlina Zahar; Harbeng Masni (Universitas Batanghari, 2022)
This research aims to describe the value of ethics in the book collection of Jambi Folklore 2 by Kaslani which refers to the ethics of human relations with society consisting of help each other, compassion, grace, and responsibility. This research includes a type of descriptive research that is qualitative. The primary data in this research is in the form of written data in the form of sentences, words, and paragraphs in the form of dialogues and monologues that are integrated in the book collection of Jambi Folklore 2, while the secondary data is in the form of books and literature taken from libraries where theories are interconnected with this research. Based on the results of the research, it can be concluded that the ethical value contained in the book collection of Jambi Folklore 2 is studied in terms of human relations with society which includes the ethics of helping each other, compassion, grace, and responsibility where all this is strengthened also by exposure to dialogue and monologues. Moreover, there are 88 expressions occured in this book, namely 15 expressions of helping each other, 17 expressions of compassions, 35 expressions of grace, 21 expressions of responsibility.